Learn more about

Refine search


Results (1-50 of 987 matches)

Next   Download to        
Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
249.a.6723.1 249.a \(y^2 + (x^3 + 1)y = -x^5 + x^3 + x^2 + 3x + 2\) $\mathrm{USp}(4)$ $0$
294.a.8232.1 294.a \(y^2 + (x^3 + 1)y = -2x^4 + 4x^2 - 9x - 14\) $G_{3,3}$ $0$
360.a.6480.1 360.a \(y^2 + (x^3 + x)y = -3x^4 + 7x^2 - 5\) $G_{3,3}$ $0$
394.a.3152.1 394.a \(y^2 + (x + 1)y = -x^5\) $\mathrm{USp}(4)$ $0$
427.a.2989.1 427.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 5x^3 + 4x^2 + 4x - 4\) $\mathrm{USp}(4)$ $0$
450.a.2700.1 450.a \(y^2 + (x^3 + 1)y = x^5 + 3x^4 + 3x^3 + 3x^2 + x\) $G_{3,3}$ $0$
484.a.1936.1 484.a \(y^2 + y = x^6 + 2x^4 + x^2\) $G_{3,3}$ $0$
555.a.8325.1 555.a \(y^2 + (x + 1)y = 3x^5 - 2x^4 - 4x^3 + x^2 + x\) $\mathrm{USp}(4)$ $0$
578.a.2312.1 578.a \(y^2 + (x^2 + x)y = x^5 - 2x^4 + 2x^3 - 2x^2 + x\) $G_{3,3}$ $0$
604.a.9664.1 604.a \(y^2 + (x^2 + x + 1)y = 4x^5 + 9x^4 + 48x^3 - 4x^2 - 53x - 21\) $\mathrm{USp}(4)$ $0$
604.a.9664.2 604.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ $0$
644.a.2576.1 644.a \(y^2 + (x^2 + x)y = -5x^6 + 11x^5 - 20x^4 + 20x^3 - 20x^2 + 11x - 5\) $G_{3,3}$ $0$
676.a.5408.1 676.a \(y^2 + (x^3 + x^2 + x)y = x^3 + 3x^2 + 3x + 1\) $G_{3,3}$ $0$
688.a.2752.1 688.a \(y^2 + y = 2x^5 - 5x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ $0$
708.a.2832.1 708.a \(y^2 + (x^2 + x + 1)y = x^5\) $\mathrm{USp}(4)$ $0$
720.a.6480.1 720.a \(y^2 + (x^3 + x)y = 2x^4 + 7x^2 + 5\) $G_{3,3}$ $0$
726.a.1452.1 726.a \(y^2 + (x^2 + 1)y = 2x^5 + 2x^4 + 6x^3 - 2x^2 - x\) $G_{3,3}$ $0$
762.a.3048.1 762.a \(y^2 + (x^3 + x^2 + x)y = x^2 + x + 1\) $\mathrm{USp}(4)$ $0$
768.a.1536.1 768.a \(y^2 + y = 2x^5 - x^4 - 3x^3 + x\) $\mathrm{USp}(4)$ $0$
768.a.4608.1 768.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2 - x - 1\) $\mathrm{USp}(4)$ $0$
784.a.1568.1 784.a \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - 2\) $G_{3,3}$ $0$
800.a.1600.1 800.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x^2\) $G_{3,3}$ $0$
800.a.8000.1 800.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^6 + 2x^4 + 4x^3 + 2x^2 - 1\) $G_{3,3}$ $0$
807.a.2421.1 807.a \(y^2 + (x^3 + x)y = x^5 - 2x^3 - x^2 + 2x - 1\) $\mathrm{USp}(4)$ $0$
830.a.6640.1 830.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 - 2x^2 + x + 1\) $\mathrm{USp}(4)$ $0$
834.a.1668.1 834.a \(y^2 + (x^3 + 1)y = -x^2 + x - 1\) $\mathrm{USp}(4)$ $0$
847.b.9317.1 847.b \(y^2 + (x^2 + 1)y = x^5 + 2x^4 - 3x^3 + 2x^2 - x\) $G_{3,3}$ $0$
847.c.9317.1 847.c \(y^2 + (x^3 + x^2)y = x^4 + x^3 - x - 2\) $\mathrm{USp}(4)$ $0$
856.a.1712.1 856.a \(y^2 + (x^3 + x)y = -x^4 - x^3 + x\) $\mathrm{USp}(4)$ $0$
862.a.6896.1 862.a \(y^2 + (x^2 + x)y = 4x^5 + 6x^4 - 3x^2 - x\) $\mathrm{USp}(4)$ $0$
864.a.1728.1 864.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^2\) $N(G_{1,3})$ $0$
886.a.3544.1 886.a \(y^2 + (x^3 + x)y = -x^4 - x + 1\) $\mathrm{USp}(4)$ $0$
909.a.8181.1 909.a \(y^2 + xy = 3x^5 - 7x^4 + x^3 + 6x^2 - 3x\) $\mathrm{USp}(4)$ $0$
932.a.3728.1 932.a \(y^2 + y = x^6 - 2x^5 + x^4 + x^2 - x\) $\mathrm{USp}(4)$ $1$
936.a.1872.1 936.a \(y^2 + (x^3 + x)y = -x^6 - 9x^4 - 32x^2 - 39\) $G_{3,3}$ $0$
968.a.1936.1 968.a \(y^2 + y = x^6 - x^4\) $G_{3,3}$ $1$
970.a.1940.1 970.a \(y^2 + (x + 1)y = x^5 + x^4 + x^3 + x^2\) $\mathrm{USp}(4)$ $0$
980.a.7840.1 980.a \(y^2 + (x^2 + x + 1)y = -x^6 + 3x^5 - 3x^4 - x\) $G_{3,3}$ $0$
990.a.8910.1 990.a \(y^2 + (x^2 + x)y = 3x^5 + 4x^4 + 7x^3 + 4x^2 + 3x\) $G_{3,3}$ $0$
1012.a.4048.1 1012.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + x^2 + x\) $\mathrm{USp}(4)$ $0$
1038.a.1038.2 1038.a \(y^2 + (x^3 + 1)y = x^4 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ $0$
1038.a.1038.1 1038.a \(y^2 + (x^2 + x)y = x^5 - 12x^4 + 26x^3 + 46x^2 + 21x + 3\) $\mathrm{USp}(4)$ $0$
1042.a.1042.1 1042.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 + 2x + 2\) $\mathrm{USp}(4)$ $0$
1047.a.3141.1 1047.a \(y^2 + (x^3 + x)y = x\) $\mathrm{USp}(4)$ $0$
1051.a.1051.1 1051.a \(y^2 + y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ $1$
1051.b.1051.1 1051.b \(y^2 + (x + 1)y = -x^5 - x^4\) $\mathrm{USp}(4)$ $0$
1051.b.1051.2 1051.b \(y^2 + xy = x^5 + 8x^4 + 16x^3 + x\) $\mathrm{USp}(4)$ $0$
1055.a.1055.1 1055.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - x - 1\) $\mathrm{USp}(4)$ $0$
1062.a.6372.1 1062.a \(y^2 + (x^3 + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ $1$
1069.a.1069.1 1069.a \(y^2 + (x^2 + x + 1)y = x^5 + x^3\) $\mathrm{USp}(4)$ $0$
Next   Download to